Soil Carbon Forms and Organic Matter Distribution in Arable Soils of Rigachikun, Northern Kaduna, Nigeria - S. N. Obasi; G. E. Jokthan; C. C. Obasi; C. O. Madueke (Bulgarian Journal of Soil Science, 2022)
The study was done in Rigachikun Kaduna, Northern Guinea Savanna and intended to investigate the carbon forms such as Organic carbon, carbon loss on ignition (LOI), Biomass microbial carbon (BMC) as well as organic matter distribution of the studied soils. A reconnaissance survey was carried out in the study location using the developed Digital Elevation Model (DEM). Soils were delineated into mapping units using the cropping land uses namely maize, cowpea and rice. In each of the cropping land use, three profile pits were sited giving a total of nine profile pits. Organic carbon contents of investigated soils were low and decreased down the horizon in all investigated pedons. This trend follows closely to organic matter which decreased in the same pattern with the values of organic carbon. Carbon LOI had a very highly significant relationship with BMC and OM, non-significantly correlated with Carbon/Nitrogen ratio, Clay, pH, K, Na and total exchangeable acidity (TEA). Biomass carbon had a negative and significant correlation with organic carbon, very highly and significant correlation with organic matter. BMC tolled the path of LOI in its relationship with other soil properties investigated. Also, all carbon forms (LOI, BMC, OC and OM) investigated exhibited high (CV > 35%) coefficient of variation in all investigated locations except in pedon 3 of location B where BMC varied moderately and pedons 1 and 2 of Location C (Rice soils) where they all varied moderately (CV >15 ≤ 35%). Generally organic matter content of the soils was very low resulting from continual use of crop litters in the feeding of farm animals rather than incorporating them to the soils. Soil degradation, erosion and desert encroachment have also affected soil of north western Nigeria so immensely.